Patterns of homosexually acquired gonococcal serovars in Edinburgh 1986-90. Issue 4 (August 1991) - Young, H; Moyes, A; Ross, J D; McMillan, A
Abstract : AIM--The aim of this study was to observe the changes in gonococcal serovar pattern in homosexual men over a 5 year period. METHODS--All men who presented to the Genitourinary Medicine clinic at Edinburgh Royal Infirmary between 1986 and 1990 with homosexually acquired gonococcal infection were included in the study. Gonococcal isolates were serotyped and the temporal change in isolated serovars noted. RESULTS--Over the 5 year period 32 different serovars were associated with 175 homosexually acquired infections. There was a dynamic temporal change in the dominant serovars with a continual influx of new strains some of which become established in the community but most of which appeared only transiently. Rapid variation in incidence over time was observed for certain serovars while others remained at more constant levels. There was a marked association between certain serovars (Ae/Av; Back/Bropyt; Bacejk/Brpyut; Bacejk/Brpyust; Baejk/Brpyut) and homosexually acquired infection. CONCLUSIONS--Possible determinants for the patterns observed are discussed but the underlying mechanism is probably multifactorial.